Distributed locating algorithm for wireless sensor networks-MDS-MAP（D） - MA Zhen; LIU Yun; SHEN Bo (Tongxin xuebao)
A new distributed locating algorithm MDS-MAP（D） was proposed,which attempted to improve the perform-ance of node localization in wireless sensor networks.The process of the computation about node relative coordinates and the aggregation from local network to global network are introduced explicitly.Further,the analyses to computational complexity and the simulations of the algorithm are also present.MDS-MAP（D）,which is based on node clustering mechanism and uses connectivity of nodes to estimate the coordinates of nodes,reduces the complexity and energy con-sumption of node localization on the absence of distance measurement with high precision.The simulation and analysis results indicate that the complexity of node localization algorithm falls to O（Nm 2）,m < N from O（N 3） and the accu-racy is improved 1%～3%.